How should we follow-up asymptomatic metal-on-metal hip resurfacing patients? A prospective longitudinal cohort study - Low, A; Matharu, G; Ostlere, S; Murray, D; Pandit, H (Elsevier, 2015)
Current surveillance for metal-on-metal hip resurfacing (MoMHR) patients is not evidence based. This study established changes that occurred in 152 asymptomatic MoMHRs using repeat ultrasound and patient-reported outcomes. Factors associated with (1) ultrasound progression and (2) developing new pseudotumors were analyzed. Patients underwent repeat assessments 4.3 years later. Ultrasound progression was observed in 19% (n = 29), with 10% (n = 15) developing new pseudotumors. Key predictors of ultrasound progression included high blood cobalt (P = .00013) and chromium (P = .00065), and high initial ultrasound grade (P = .003) and volume (P = .036). No asymptomatic MoMHRs with initially normal metal ions (< 2 μg/L) and normal ultrasounds (33% of cohort) developed new pseudotumors. This patient subgroup does not require repeat follow-up within 5 years.